Peran Komunikasi dalam Membangun Keberlanjutan dan Ketahanan Lingkungan - Mahardhika Sastra Nasution; Hasan Sazali (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Environmental sustainability and sustainable development are the main problems in the world today. Environmental damage caused by human activities has reached an alarming level. Collective action is needed to restore ecological balance and protect the planet for future generations. Communication plays an important role in achieving environmental sustainability and sustainability. Effective communication can increase public awareness of environmental issues, encourage public participation in environmental projects, and facilitate cooperation between different interest groups. The aim of this research is to consider the role of communication in building sustainability and environmental sustainability. The importance of communication in increasing environmental awareness can help people understand the impact of human activities on the environment and the importance of nature conservation. The role of communication in encouraging community participation can motivate people to participate in environmental activities such as recycling, energy efficiency and environmental activities. Facilitating cooperation between different communication actors can bring together various related parties, such as the state, NGOs, the private sector and society, to jointly solve environmental problems. Communication is an important tool for building sustainability and environmental sustainability. Communication can help us achieve a greener and more sustainable future by raising awareness, encouraging community participation and facilitating collaboration.